Implementing the 12-Year Compulsory Education Policy in Kaimana : Opportunities and Challenges - Randy Lieminarto; Sarwani Sarwani; Ulul Albab (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to explore the implementation of the 12-Year Compulsory Learning policy in Kaimana Regency, West Papua, with a focus on the challenges and opportunities faced by the Finance Section of the Education, Youth, and Sports Office in managing the education budget. This study also examines how budget management and allocation of education funds can improve access and quality of education in the area, as well as the role of coordination between local governments, schools, and communities. A qualitative approach with a case study design was used in this study to collect data through in-depth interviews, participatory observation, and document analysis. The results of the study show that despite efforts to improve performance-based budget management, limited infrastructure and human resources remain the main challenges in the implementation of education policies. Weak coordination between stakeholders, as well as active community involvement, are important factors influencing the success of the 12-Year Compulsory Learning policy. This study recommends increasing the capacity of human resources, allocating more equitable budgets, and strengthening collaboration between local governments, schools, and communities to increase the effectiveness of these policies. Thus, this research contributes to a deeper understanding of the implementation of education policies in remote areas and proposes practical solutions to address existing challenges. Furthermore, this study highlights the importance of transparency and accountability in education budget management as an effort to build public trust and ensure that available funds are truly used to support improvements in education quality. In the context of Kaimana Regency, which faces geographical challenges and limited access, a participatory oversight mechanism involving the community and independent oversight institutions is key to ensuring that budget allocations are not only on target but also capable of driving real change on the ground.